Tax on employee share options. - Fun, Yin Chia. (2008)
This paper addresses how employee share options are taxed in different countries and gives a suggestion on how share options in Singapore should be taxed to complement government policies. A comparison between taxation treatment in the United Kindom, Australia and Singapore is presented to provide ideas of possible changes.